052 Exploring the genetic basis of pharmacoresistance in epilepsy: an integrative analysis of large-scale gene expression profiling studies on brain tissue from epilepsy surgery. Issue 3 (9th February 2012) - Mirza, N; Vasieva, O; Marson, A G; Pirmohamed, M
Abstract : The biological processes underlying the development of pharmacoresistance in epilepsy are poorly understood, but multiple interconnected genes and pathways are likely to be involved. At least 12 microarray studies on brain tissue from epilepsy surgery have been performed in order to investigate the causes of epilepsy pharmacoresistance, but they have failed to make a significant impact because (1) doubts have been raised about their reproducibility, (2) only a small number of the gene expression changes found in each microarray study have been independently validated, and (3) the results of different studies have not been integrated to give a coherent picture of the genetic changes involved in epilepsy pharmacoresistance. To overcome these limitations, we (1) assessed the reproducibility of the included microarray studies: we calculated the size of the overlap between lists of differentially regulated genes from pairs of microarray studies and determined if this is greater than would be expected by chance alone, (2) used an inter-study cross-validation technique to simultaneously verify the expression changes of large numbers of genes, (3) used the combined results of the different microarray studies to perform an integrative analysis based on enriched Gene Ontology terms, networks and pathways. Using these techniques, we have respectively (1) demonstrated that there are statistically significant overlaps between the gene expression changes in different publications, (2) simultaneously verified the differential expression of 233 genes, (3) identified the biological processes, networks and genes likely to be most important in the development of pharmacoresistant epilepsy.